Flood-tech frontiers: smart but just? A systematic review of AI-driven urban flood adaptation and associated governance challenges - Johannes Bhanye (Discover Global Society)
Abstract As rising waters meet rising technologies, a new “flood-tech frontier” is emerging at the intersection of climate risk and digital innovation. Across many cities, especially, in the Global South, extreme weather events and rapid urbanization have turned flooding into a persistent crisis. In this context weak infrastructure, informal settlements and limited governance capacities are also exacerbating vulnerabilities. In recent years, Artificial Intelligence (AI) has gained attention as a promising solution in flood risk management, offering capabilities in real-time prediction, risk assessment, decision support, and community engagement. Yet, scholarly discourse remains fragmented, overly technocentric, and insufficiently attuned to governance and justice concerns. This study presents a rapid systematic review of 20 peer-reviewed studies published between 2014 and 2024, focusing on how AI technologies are applied across the urban flood adaptation cycle: forecasting, vulnerability assessment, planning, response, and recovery, and the governance challenges that shape their effectiveness. The review identifies a diverse set of AI techniques, including machine learning (ML), deep learning (DL), geospatial AI, and AIoT, used in both Global North and South cities. Findings reveal that while AI enhances predictive precision and speeds up decision-making, its effectiveness is highly context-dependent, constrained by data quality, model transparency, digital inequalities, and institutional readiness. The study introduces a socio-technical systems perspective that frames AI not as a neutral tool but as a governance actor embedded in systems of power, planning, and exclusion. Key limitations include the poor transferability of AI models across geographies, a lack of participatory design, and risks of algorithmic exclusion in already marginalized urban areas. The paper concludes by proposing a justice-oriented framework for AI governance in urban climate adaptation, one that integrates ethics, equity, and local engagement into the design and deployment of digital technologies. The review contributes to rethinking AI-driven urban flood adaptation not just as a technical challenge but as a political and governance frontier. It argues that building resilient cities requires more than smart systems, it demands just systems, especially for those most at risk. To this end, the paper calls for deeper integration of co-produced knowledge, adaptive planning, and climate justice principles at the flood-tech frontier.